Artificial Intelligence in Climate Change Communication: Enhancing Public Awareness, Participation, and Policy Engagement - Mohammad Nawab Turan; Omid Tarashtwal; Hafizullah Shahbazi (Balai Publikasi Indonesia, 2026)
Climate change remains one of the most pressing global challenges, yet public awareness, participation, and evidence-based policy engagement often lag due to the complexity of scientific information and ineffective communication strategies. This study explores the role of artificial intelligence (AI) in enhancing climate change communication, fostering citizen engagement, and supporting policy formulation. Using a systematic literature review (SLR) methodology, publications from 2010 to 2025 were collected from reputable databases, including ScienceDirect, SpringerLink, IEEE Xplore, MDPI, Wiley, Emerald, and Scopus. Boolean search operators and targeted keywords, such as “artificial intelligence,” “climate change communication,” “public engagement,” and “policy,” guided the selection of relevant studies. Results indicate that AI significantly improves public understanding by enabling data-driven visualization, natural language generation, and predictive analytics. It enhances citizen participation through AI-powered citizen science initiatives, collaborative data collection, and real-time monitoring of environmental indicators. Additionally, AI strengthens policy engagement by facilitating evidence-based governance, scenario modeling, and adaptive decision-making. Overall, AI functions as a transformative tool that bridges scientific knowledge, societal awareness, and policy implementation, promoting informed and sustainable climate action. The findings underscore the need for equitable access, ethical considerations, and capacity building to ensure that AI benefits are widely shared and contribute to resilient climate strategies.